2002
DOI: 10.1152/ajpgi.00370.2001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase-2 ameliorates the severity of pancreatitis and associated lung injury

Abstract: Inhibition of cyclooxygenase-2 ameliorates the severity of pancreatitis and associated lung injury. Am J Physiol Gastrointest Liver Physiol 283: G1166-G1174, 2002. First published July 17, 2002 10.1152/ajpgi.00370.2001.-Cyclooxygenase-2 (COX-2), a widely distributed enzyme, plays an important role in inflammation. We have studied the role of COX-2 in acute pancreatitis and pancreatitis-associated lung injury using both the pharmacological inhibition of COX-2 and genetic deletion of COX-2. Pancreatitis was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 37 publications
2
60
1
4
Order By: Relevance
“…Hematoxylin and eosin-stained sections of pancreas and lungs were evaluated microscopically by a person unaware of the treatment. The extent of injury was calculated by morphometry as described earlier (22). Pancreatic sections were stained for collagen with Sirius red as described by Junqueira et al (10).…”
Section: Induction Of Pancreatitis In Micementioning
confidence: 99%
“…Hematoxylin and eosin-stained sections of pancreas and lungs were evaluated microscopically by a person unaware of the treatment. The extent of injury was calculated by morphometry as described earlier (22). Pancreatic sections were stained for collagen with Sirius red as described by Junqueira et al (10).…”
Section: Induction Of Pancreatitis In Micementioning
confidence: 99%
“…Many studies show that injury of the over activated neutrocyte on self tissue is an important cause of systemic complications due to AP (Chen et al, 2001;de Dios et al, 2002;Descamps et al, 2003;Ammori, 2003;Shields et al, 2001;Demols and Deviere, 2003;Zhao et al, 2003;Zhou et al, 2002;Song et al, 2002;Brady et al, 2002;Clemons et al, 2002;Hartwig et al, 2002c;Mikami et al, 2002). The neutrophilic granulocyte stimulated by pancreatitis can release inflammatory cytokines such as TNF-α (Cassatella, 1995;Ni et al, 1998;Ogawa, 1998).…”
Section: Neutrophilic Infiltration and Generation Of Cytokinesmentioning
confidence: 99%
“…Previous experimental studies on mice [13,14] have shown that pharmacological inhibition of COX-2 or COX-2 gene disruption ameliorates the severity of pancreatitis and the pancreatitis-associated lung injury. In contrast, in the rat model of pancreatitis, Foitzik et al [32] , have found some beneficial systemic effects of COX-2 inhibition on acute pancreatitis, such as an improvement of renal and respiratory function, but they have not observed any significant effect of COX-2 inhibition on histological score of pancreatic damage or plasma level of trypsinogen activation peptides.…”
Section: Effect Of Ischemic Preconditioning and Cerulein-induced Pancmentioning
confidence: 98%
“…The role of COX-2 in pancreatic pathology is unclear. Studies performed by Song et al [13] , and Ethridge et al [14] , with mice have shown that pharmacological inhibition of COX-2 or COX-2 gene disruption reduces the severity of pancreatitis and pancreatitis-associated lung injury. On the other hand, our own study has shown that inhibition of COX-2 abolishes the protective effect of hepatocyte growth factor (HGF) against cerulein-induced pancreatitis [15] .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%